2019
DOI: 10.3748/wjg.v25.i47.6857
|View full text |Cite
|
Sign up to set email alerts
|

Direct costs of carcinoid syndrome diarrhea among adults in the United States

Abstract: BACKGROUNDThe burden of carcinoid syndrome (CS) among patients with neuroendocrine tumors is substantial and has been shown to result in increased healthcare resource use and costs. The incremental burden of CS diarrhea (CSD) is less well understood, particularly among working age adults who make up a large proportion of the population of patients with CS.AIMTo estimate the direct medical costs of CSD to a self-insured employer in the United States.METHODSCS patients with and without CSD were identified in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…This study also indicated that patients with recurrent disease suffered from significant fatigue, and impaired sleep and physical functioning. Another study indicated that the economic burden of CS was 50% higher among patients with diarrhea, than that of CS with another symptom among insured working age adults in the United States 87 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study also indicated that patients with recurrent disease suffered from significant fatigue, and impaired sleep and physical functioning. Another study indicated that the economic burden of CS was 50% higher among patients with diarrhea, than that of CS with another symptom among insured working age adults in the United States 87 …”
Section: Methodsmentioning
confidence: 99%
“…Another study indicated that the economic burden of CS was 50% higher among patients with diarrhea, than that of CS with another symptom among insured working age adults in the United States. 87 Patients with CS have different symptoms, treatment side effects, and emotional and functional concerns compared to patients with other neoplastic diseases. A recent study aimed to identify the highest priority symptoms and concerns of patients with CS by developing the Functional Assessment of Cancer Therapy-Carcinoid Syndrome Symptom Index.…”
Section: Treatment Strategies For Syndrome Control and Multidisciplin...mentioning
confidence: 99%
“…The total adjusted annual healthcare cost per patient was 50% higher among those with carcinoid syndrome diarrhoea, mainly driven by outpatient services, prescriptions and ED visits. (Dasari et al, 2019) CS negatively impacts the patient and the healthcare system. Timely identification and management of carcinoid syndrome and CS related diarrhoea may reduce the economic burden.…”
Section: Chemotherapymentioning
confidence: 99%
“… 6 CS diarrhea and flushing are the most common and disruptive symptoms of CS, with CS diarrhea having a substantial negative impact on quality of life. 2 Patients with CS diarrhea are hospitalized more often and incur higher overall healthcare costs than those without CSD, 7 , 8 and experience impairment in work productivity and indirect costs, 9 reinforcing the need for more effective management of CS.…”
Section: Introductionmentioning
confidence: 99%